Quality of ambulatory prevention and treatment of cardiovascular disease and its complications among Туре 2 diabetes mellitus patients - R. G. Oganov; V. K. Lepakhin; S. B. Fitilev; A. M. Levin; I. I. Shkrebneva; Yu. Yu. Titarova; Yu. Yu. Tsiruleva (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To evaluate the real-world clinical practice implementation of modern international and national recommendations on primary and secondary prevention and pharmacotherapy of cardiovascular disease (CVD) among patients with Type 2 diabetes mellitus (DM-2) in one administrative area of Moscow City (2004-2006).Material and methods. Cross-sectional retrospective analysis of ambulatory medical card data was performed among 1146 DM-2 patients attending one out of three Moscow City South-West Area policlinics (2004-2006). Quality of primary and secondary prevention and pharmacotherapy was assessed by compliance with modern international and national standards. The following data from ambulatory medical cards were analyzed: general information on the patient, main risk factors (RFs), comorbidities, instrumental and laboratory tests and their results, number of hospitalizations and sick-leaves, administered therapy.Results. Ambulatory cards contained inadequate information on RFs and recommendations on RF correction. Alcohol consumption and smoking were mentioned only in 0,53 % and 6,19 % of the cases, respectively. Recommendations on reducing alcohol consumption were recorded for 0,70 %, smoking cessation - for 1,83 %, and salt intake reduction - for 2,44 %. Body weight control was recommended in 1,05 % of the cases only, despite overweight and obesity prevalence of 30 % and >45 %, respectively. The levels of blood pressure (BP), lipids, fasting glucose, glycated hemoglobin (HbAlc) were higher than respective target levels stated in national and international recommendations. Target level of BP was achieved in 4,36 % of DM-2 patients, low-density lipoprotein cholesterol - in 18,35 %, fasting glucose - in 27,67 %, and HbAlc - in 24,80 %.Conclusion. Real-world clinical practice of ambulatory treatment of DM-2 patients was not consistent with modern international and national standards of CVD prevention and therapy.